The Jaw Tumor: A Surgical and Oncologic perspective (Journal of Bio-Science, 2015)
The Jaw tumor is now a very well-known entity in the field of medicine and Called Burkitt Lymphoma Syndrome or Burkitts lymphoma (BL). It is a highly aggressive non-Hodgkins lymphoma and is the fastest growing tumors in children especially in East Africa. This is the first malignant extra nodal lymphoma in which Epstein-Barr virus has been detected specially in the tumors of East African origin. The discovery of EBV is the Burk kits tumor is another progress that has been MADE THE MEDICAL COMMUNITY to understand the disease process. EBV virus may be playing a role as an oncogene for this disease by retranslocating or translocation the c-MYC gene. Early days when such tumor is introduced by Dennis Burkitt before the medical community there was no real pathological classification, immumohistochemical or biological study. Subsequently it was felt that a chromosal translocation that activates an oncogene called e-MYC is the etiology of such tumor. But current molecular study shows that there are other oncogenes that are involved in the development of this deadly ailment especially in western countries. Our knowledge of BL was inadequate in early years of discovery of BL and so as well our diagnosis and treatment. In early stage of discovery of BL there were very limited option of treatment from local radical surgery, local radiation( which was not available in Uganda during that time) to only two chemotherapies and 5 years of survival rate was only 10%.But with our current knowledge of molecular biology of this malignancy there are multiple options of treatment such as combination of various chemotherapies, monoclonal antibodies either alone and or in combination and with either complete removal of tumor or debunking procedure specially abdominal neoplasm, the current 5 years survival rate is about 90%.This very brief review article describes the background, clinical feature, histology ,molecular study as it relates to prognosis and current treatment of both Burkitts tumor and extra nodal abdominal tumor both based on experience of our group in late seventies of treating few cases of devastating abdominal BL and review of few scholarly article on BL. DOI: http://dx.doi.org/10.3329/jbs.v21i0.22513 J. bio-sci. 21: 01-19, 2013